2022
DOI: 10.1186/s12872-022-02780-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk probability and influencing factors of stroke in followed-up hypertension patients

Abstract: Objective To explore the risk probability and main influencing factors of stroke in followed-up hypertension patients through the analysis of long-term followed-up cohort data. Methods The method of followed-up observation cohort was used to collect the information of 168,417 followed-up hypertension patients from 2002 to 2020 in Jiading District in Shanghai. Kaplan–Meier method was used to analyze the risk probability of stroke complications in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Generally, subjects with FHS were shown to accumulate risk factors over time [ 54 ]. The most frequently reported of these in subjects with FHS was hypertension [ 8 , 9 , 15 , 45 , 55 - 58 ]. This association was supported by evidence of aggregation of stroke and hypertension in families [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, subjects with FHS were shown to accumulate risk factors over time [ 54 ]. The most frequently reported of these in subjects with FHS was hypertension [ 8 , 9 , 15 , 45 , 55 - 58 ]. This association was supported by evidence of aggregation of stroke and hypertension in families [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypertension [8,9,15,45,[55][56][57][58] FHS is associated with increased prevalence of hypertension.…”
Section: Family History Of Stroke In Primary Stroke Preventionmentioning
confidence: 99%
“…Moreover, while smoking rates in Vietnam are relatively high, the current study observed a higher prevalence of smoking among Caucasians, potentially implicating the influence of acculturation on lifestyle changes. Hypertension, a well-established stroke risk factor [ 15 ], was observed at higher rates in a US-based study, with Filipino and Vietnamese individuals more likely to have hypertension compared to other ethnic minority groups [ 16 ]. Hypertension is also a significant public health concern among Vietnamese adults domestically, being the third leading contributor to cause of death in Vietnamese hospitals among adults [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that hypertension is a risk factor for stroke. Patients with hypertension are substantially more susceptible to suffering a stroke than those with normal blood pressure ( 14 ). In a study of the lifetime risk of coronary heart disease, the lifetime risk of coronary heart disease in male hypertensive patients was 26.95% and the lifetime risk of coronary heart disease in female hypertensive patients was 14.85%, both of which were higher than the average level ( 15 ).…”
Section: Discussionmentioning
confidence: 99%